DEVELOPMENT OF SAIQU TEACHING MATERIALS BASED ON PROBLEM-BASED LEARNING ON THE TOPIC "BEHAVIOR HONEST, TRUSTWORTHY, AND CONSISTENT" AT SMP-IT PELITA DOKTORA - Sukarno; Melia Wati, Salma (Jurnal Pelita Pendidikan, 2025)
This research focuses on the development of SAIQU (Science and Quran) teaching materials for the topic of "Behaving honestly, trustworthy, and consistently" in Islamic Religious Education and Character Education subjects at the Junior High School (SMP) level. The Research and Development (R&D) method is used with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The teaching materials were validated by three experts in Islamic religious education, natural sciences, and language. The validation results show that the SAIQU teaching materials meet excellent eligibility standards regarding content, language, integration of Islamic values ​​with scientific concepts, and presentation appearance. This material successfully combines scientific and spiritual elements harmoniously. This material can also stimulate active student involvement through experimental activities, observation, and contemplation of kauniyah verses. Through this approach, students gain a deeper understanding of concepts and develop religious character and the critical, reflective, and collaborative thinking skills needed to face the challenges of the 21st century. Therefore, SAIQU teaching materials are considered appropriate as contextual learning media to support the implementation of the Independent Curriculum in Islamic educational settings.